A study of the student teaching program of the Northern Luzon Teachers College - Bonoan, Vicente A. 1935- (s.n.], 1969)
The author assessed the strengths and weaknesses of the student teaching program of the Northern Luzon Teachers College operating in Northern Luzon provinces of Abra, Apayao-Kalinga, Batanes, Cagayan, Ilocos Sur, Isabela, and Ilocos Norte in order to recommend measures of improvement.